2012
DOI: 10.1093/geronb/gbs094
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Physical Functioning Among Older Adults: The Moderating Role of Education

Abstract: This study is the first to support a vulnerability model, which entails an amplification of neuroticism risk at low education, but a diminishment of neuroticism risk for activity limitations at high education. As a whole, it appears that a focus on either personality or education without taking into account each other provides only a partial account of the predictors of basic daily physical activities in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 17 publications
4
23
0
Order By: Relevance
“…In another sample, Openness, Extraversion, and Neuroticism moderated associations between stress and health behaviors (Korotkov, 2008). In a French sample, although Neuroticism related to worse physical functioning, this effect was amplified at low levels of education and diminished at high levels of education (Jaconelli, Stephan, Canada, & Chapman, 2013). In a group of children and adolescents, associations between prosocial behavior, externalizing problems, internalizing problems, and grades were moderated by the early family environment, with effects being stronger in more difficult circumstances (Slobodskaya, Ashmetova, & Rippinen, 2014).…”
Section: Moderatorsmentioning
confidence: 90%
“…In another sample, Openness, Extraversion, and Neuroticism moderated associations between stress and health behaviors (Korotkov, 2008). In a French sample, although Neuroticism related to worse physical functioning, this effect was amplified at low levels of education and diminished at high levels of education (Jaconelli, Stephan, Canada, & Chapman, 2013). In a group of children and adolescents, associations between prosocial behavior, externalizing problems, internalizing problems, and grades were moderated by the early family environment, with effects being stronger in more difficult circumstances (Slobodskaya, Ashmetova, & Rippinen, 2014).…”
Section: Moderatorsmentioning
confidence: 90%
“…Previous studies have consistently reported that emotional stability (low levels of neuroticism), extraversion, and conscientiousness are positively related to better physical functioning of older adults (Friedman, Kern, & Reynolds, 2010; Jaconelli, Stephan, Canada, & Chapman, 2013; Magee, Heaven, & Miller, 2013) and conscientious older adults are more likely to better take care of themselves and sustain a healthier lifestyle, which will lead them to age successfully (Martin, 2007). In addition, in both cross-sectional and longitudinal studies, researchers have consistently reported that high levels of neuroticism or negative affectivity (e.g., anxiety, anger, depression, and hostility) have an influence on heart disease, cancer, high blood pressure, and negative health behaviors such as smoking, which can subsequently increase mortality (Aldwin, Spiro, Levenson, & Cupertino, 2001; Scheier & Bridges, 1995; Smith, Glazer, Ruiz, & Gallo, 2004).…”
Section: Personality Traits and Successful Agingmentioning
confidence: 99%
“…The vulnerability model shows an ampli cation of neuroticism risk in those with low education, but a decrease of neuroticism risk for higher education. This strongely suggest the a positive association between education levels and character strengths [27] . In the adult employees, the effect of character strengths on earnings was regulated by gender, namely, women's earnings were strongly affected by character strengths, while the effect of character strengths on men's earnings was small and not always signi cant [28] .…”
Section: Discussionmentioning
confidence: 76%